Pelatihan Penggunaan AI untuk Mendukung Pembelajaran di Tingkat Sekolah Dasar Lab Undiksha - Sindu, I Gede Partha; Permana, Agus Aan Jiwa; Kertiasih, Ni Ketut; Setemen, Komang; Pracasitaram, Gede Made Surya Bumi (Al-DYAS, 2025)
The community service activity titled Training on the Use of AI to Support Learning at the Elementary School Level, conducted at the Undiksha Laboratory School, was driven by the urgent need to enhance teachers’ competencies in response to rapid developments in digital technology, particularly generative artificial intelligence (generative AI). Teachers are expected to integrate technology into the educational process to make learning more effective, relevant, and innovative. The primary goal of this activity was to equip elementary school teachers with both conceptual understanding and practical skills in utilizing AI as a tool to support learning. The training was structured around four core topics: basic introduction to AI, the use of AI in lesson planning, AI-assisted development of interactive learning media, and practical application of AI-based tools. The implementation methods included material delivery, active discussions, and hands-on practice to ensure a balance between theory and application. Evaluation results showed a significant improvement in participants’ understanding and skills related to AI usage, increased motivation to innovate in teaching, and strengthened technological orientation in classroom practice. Participants also appreciated the training as a valuable initiative and recommended its continuation. Therefore, this training has made a tangible contribution to enhancing teacher capacity and supporting the transformation of learning at the elementary school level.